KAJIAN KEPEMIMPINAN WALIKOTA PEKALONGAN DALAM MEWUJUDKAN KESEJAHTERAAN MASYARAKAT - MUHAMMAD ADNAN, MUHAMMAD ADNAN (Politika: Jurnal Ilmu Politik, 2011)
AbstractImproving people’s welfare is an important indicator for the leadership’s success of a regionalleader. With numbers of indicators, Pekalongan is one area that was considered successful under theleadership of dr. Bashir Ahmad from 2005-2010 and 2010-present. The success is determined byvarious factors both personal and environmental factors.This research was conducted to answer the problem of personality strenght aspect/politicalpersonality (microenvironment) and social environment aspect (macroenvironment)that support orreject the mayor’s political leadership, dr. Bashir ahmad. Using qualitative analysis as type ofresearch with in-depth interview and documentation study as data collecting technique.The result of this research shows that the successful leadership of dr.Bashir as mayor ofPekalongan in realizing people’s welfare with micro analysis is influenced by his personal’s characterwhich are visionary, hardworker, commited in vision and programs that has been established,unyielding, and dare taking risks. While in macro perspective, the success of bashir’s leadership isdetermined by his ability to establish patterns of good communication with parliament, NGO’s, andmass media so he can create conducive and productive climate. And in reforming the bureaucracy.Keywords: political leadership, analysis Micro-Macroenvironments